Assessment of the carotid artery intima-media complex through ultrasonography and the relationship with Pathobiological Determinants of Atherosclerosis in Youth. (11th November 2015) - Ramos, Thacira D. A.; Dantas, Tatianne M. E.; Simões, Mônica O. S.; Carvalho, Danielle F.; Medeiros, Carla C. M.
Abstract: Objective: To evaluate the presence of carotid thickening and its relationship with the Pathobiological Determinants of Atherosclerosis in Youth score. Methods: We carried out a cross-sectional study involving 512 brazilian adolescents. Variables such as sex, body mass index, concentrations of non-high-density lipoprotein and high-density lipoprotein cholesterol, blood pressure, blood glucose and glycated haemoglobin A1c levels that make up the score, and carotid thickening through the intima-media complex measured by ultrasound were evaluated. We adopted two cut-off points to evaluate carotid thickening, being considered altered for those higher or equal to the z-score 2+ and ⩾75th percentile. The association was assessed using the χ 2 test and univariate and multivariate logistic regression analyses. Results: High cardiovascular risk was present in 10.2% of the adolescents; carotid thickness was present in 4.3% determined by the z-score 2+ and in 25.0% determined by the 75th percentile. When measured by the z-score, carotid thickening was associated with high systolic blood pressure (p=0.024), high-non-high density lipoprotein cholesterol (p=0.039), and high cardiovascular risk assessed by the score and by the 75th percentile, with body mass index >30 (p=0.005). In the multivariate analysis, high cardiovascular risk was found to be independently associated with the presence of carotid thickness evaluated by the z-score, with risk four times greater (p=0.010) of presenting with this condition compared with individuals with low risk, and this fact was not observed when factors were analysed alone. Conclusion: The presence of high cardiovascular risk in adolescents assessed by the Pathobiological Determinants of Atherosclerosis in Youth score was associated with marked thickening of the carotid artery in healthy adolescents.